The potential of eye tracking for visual literacy research. Issue 1 (2nd January 2021) - Brumberger, Eva
Abstract: The multitude of disciplines, perspectives, and practices that inform the study of visual literacy is incredibly valuable, but at the same time it means our research lacks a shared set of methodologies and methods. Unfamiliar research approaches may lead to mistrust of research findings and, even more problematic, to missed opportunities for knowledge development, opportunities that are vital to progress in the field. Eye tracking is one such method that is likely to be outside the traditional disciplinary approaches of most visual literacy scholars, yet it has the potential to be productive for many of the types of questions that the field seeks to answer. Following an introduction to eye-tracking methods, terminology, and data types, the article provides an overview of past eye-tracking research that can inform visual literacy studies. The article then turns to a discussion of visual literacy research that could potentially be addressed by eye-tracking methods.